Invited commentary: Attentional capture and its suppression viewed as skills. Issue 9 (21st October 2021) - Schmid, Rebecca Rosa; Büsel, Christian; Ansorge, Ulrich
ABSTRACT: Attention – here, the selection of visual information – is necessary for the control of skills and procedures. In amendment of the principles discussed by Luck et al. [Luck, S. J., Gaspelin, N., Folk, C. L., Remington, R. W., & Theeuwes, J. (2021). Progress toward resolving the attentional capture debate. Visual Cognition, 29(1), 1–21. https://doi.org/10.1080/13506285.2020.1848949], we review evidence for this general influence: the moderating influence of stimulus awareness on attention capture by abrupt onsets; and the influence of linguistic differences between languages on stimulus-driven attention capture.